COMPARISON OF ACID-RESISTANT BACIL EXAMINATION RESULTS IN SPUTUM SUSPECTED OF INTERMEDIATE PULMONARY TUBERCULOSIS ZIEHL-NEELSEN METHOD BY METHOD GENEXPERT IN HOSPITAL TOTO KABILA DISTRICT BONE BOLANGO - Krisharianti, Vika Septiana; Malaha, Adnan; Warastuti, Rita Amini (LPPM Universitas Bina Mandiri Gorontalo, 2024)
This study aims to determine the comparison of the results of acid-resistant bacilli examination in sputum suspected of pulmonary tuberculosis in the two examination methods used to detect Mycobacterium tuberculosis, namely the Ziehl Neelsen method by staining sputum and the GeneXpert method by automatically using the GeneXpert tool on sputum suspected of pulmonary tuberculosis. The method in this study is quantitative with primary data type and sampling technique using purposive sampling with a total of 20 samples. The results showed that both examination methods, namely ziehl neelsen and geneXpert, obtained a significance value (sig.) (2-Tailed) of 0.317 which is more than the value of a (a = 0.05), or 0.317> 0.05 based on the results of statistical analysis, then H₂ is accepted and Ho is rejected.